Giving once, giving twice: A two-period field experiment on intertemporal crowding in charitable giving - Maja Adena; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
We study intertemporal crowding between two fundraising campaigns for the same charitable organization by manipulating donors' beliefs about the likelihood of future campaigns in two subsequent field experiments. The data shows that initial giving is decreasing in the likelihood of a future campaign while subse-quent giving increases in initial giving. While this refutes the predictions of a simple expected utility model, the pattern is in line with a model that allows for (anticipated or unanticipated) habit formation provided that donations in the two periods are substitutes.
Keywords: C93; D64; D12; 330; Charitable giving; field experiments; intertemporal crowding